Le nouveau calendrier des grands hommes 2 vols. - Harrison, Frederic 1831-1923; Avezac-Lavigne, Charles (Paris Leroux, 1895)
The first object of Comte was to give a concrete picture of human evolution: and, so far as is known, it is the only attempt of the kind. But it is not a class-list of rival candidates for fame. It is in no sense exclusive; it is provisional; and it is in every sense relative - framed with a view, not to personal merit, but to historical results. It must be understood that this Calendar, framed as it was in the first half of the nineteenth century, is a historical summary of the progress of civilisation down only to that date.
Keywords: Comte, Auguste -- 1798-1857; 19th Century (1801-1900); History; Sociology